2014
DOI: 10.1111/apt.12994
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of transjugular intrahepatic portosystemic shunt (TIPSS) in 40 patients with hepatocellular carcinoma

Abstract: SUMMARY BackgroundPortal hypertension and hepatocellular carcinoma (HCC) are major complications of advanced liver cirrhosis. Thus, patients are often affected by both complications. Transjugular intrahepatic portosystemic shunt (TIPSS) is an effective treatment for portal hypertension and its complications. However, no established guidelines for the treatment of symptomatic portal hypertension in HCC patients are currently available. In addition, only limited information exists about the consequence of TIPSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 55 publications
3
43
1
4
Order By: Relevance
“…However, TIPS is not only associated with intervention‐related complications but may also increase the risk for hepatic encephalopathy (HE) as compared to the standard treatment with LVP+A, although prior studies have found conflicting results . Furthermore, TIPS is not universally available and may be associated with procedural‐related complications, thus LVP+A is still considered as the current standard of care for patients with refractory ascites …”
Section: Introductionmentioning
confidence: 99%
“…However, TIPS is not only associated with intervention‐related complications but may also increase the risk for hepatic encephalopathy (HE) as compared to the standard treatment with LVP+A, although prior studies have found conflicting results . Furthermore, TIPS is not universally available and may be associated with procedural‐related complications, thus LVP+A is still considered as the current standard of care for patients with refractory ascites …”
Section: Introductionmentioning
confidence: 99%
“…4 Presence of cirrhosis, irrespective of the aetiology, results in increased risk of HCC development. [5][6][7] In India, cirrhosis in association with HCC is seen in the range of 60-97%. 4,8 Cirrhosis of all aetiologies is at risk of developing HCC and persistent hepatitis B (HBV) and C (HCV) infections are associated in 80% of HCC cases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A covered stent designed specifically for TIPS would reduce the rate of stenosis, extend long-term patency, and reduce the risk of tumor seeding within the liver, especially when the shunt traverses the malignancy, but the longterm efficacy of this treatment needs to be evaluated further. There is some dispute about whether patients with PVTT should be eligible for TIPS (62,63). A direct intrahepatic portacaval shunt (DIPS) is a modified form of TIPS that seeks to create an intrahepatic shunt between the inferior vena cava behind the liver and the portal vein.…”
Section: Interventional Creation Of a Shuntmentioning
confidence: 99%